Smart Education and e-Learning 2016 - Uskov, Vladimir L.; Howlett, Robert J.; Jain, Lakhmi C. (Smart Innovation, Systems and Technologies,, 2016)
This book contains the contributions presented at the 3rd international KES conference on Smart Education and Smart e-Learning, which took place in Puerto de la Cruz, Tenerife, Spain, June 15-17, 2016. It contains a total of 56 peer-reviewed book chapters that are grouped into several parts: Part 1 - Smart University: Conceptual Modeling, Part 2 - Smart Education: Research and Case Studies, Part 3 - Smart e-Learning, Part 4 - Smart Education: Software and Hardware Systems, and Part 5 - Smart Technology as a Resource to Improve Education and Professional Training. We believe that the book will serve as a useful source of research data and valuable information for faculty, scholars, Ph.D. students, administrators, and practitioners - those who are interested in innovative areas of smart education and smart e-learning. .